2015
DOI: 10.1111/ejn.12892
|View full text |Cite
|
Sign up to set email alerts
|

Selecting danger signals: dissociable roles of nucleus accumbens shell and core glutamate in predictive fear learning

Abstract: Conditioned stimuli (CSs) vary in their reliability as predictors of danger. Animals must therefore select among CSs those that are appropriate to enter into an association with the aversive unconditioned stimulus (US). The actions of prediction error instruct this stimulus selection so that when prediction error is large, attention to the CS is maintained and learning occurs but when prediction is small attention to the CS is withdrawn and learning is prevented. Here we studied the role of glutamate acting at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Finally, in the rostrocaudal plane, disrupting glutamatergic neurotransmission via infusions of an AMPA/Kainate receptor antagonist generates appetitively motivated behaviors (e.g., ingestion) in the rostral medial AcbSh but aversively motivated behaviors (e.g., defensive treading) in the caudal medial AcbSh (Reynolds & Berridge, , ). Interestingly, these rostrocaudal variations in valence are dopamine‐dependent (Faure et al ., ), consistent with other findings implicating AcbSh glutamate and dopamine neurotransmission in aspects of aversive learning and motivation (Li & McNally, ,b).…”
Section: Linking Dual Roles In Extinction and Reinstatement To Heterosupporting
confidence: 92%
“…Finally, in the rostrocaudal plane, disrupting glutamatergic neurotransmission via infusions of an AMPA/Kainate receptor antagonist generates appetitively motivated behaviors (e.g., ingestion) in the rostral medial AcbSh but aversively motivated behaviors (e.g., defensive treading) in the caudal medial AcbSh (Reynolds & Berridge, , ). Interestingly, these rostrocaudal variations in valence are dopamine‐dependent (Faure et al ., ), consistent with other findings implicating AcbSh glutamate and dopamine neurotransmission in aspects of aversive learning and motivation (Li & McNally, ,b).…”
Section: Linking Dual Roles In Extinction and Reinstatement To Heterosupporting
confidence: 92%
“…The effects of Acb AMPA manipulations can be explained formally by supposing that poorer predictors are associated with greater signaling via Acb AMPA receptors than better predictors, so that signaling via Acb AMPA receptors is inversely related to ∑V in the Pearce-Hall model. We (S. S. Y. Li & McNally, 2015b) conducted a variety of simulations of this action using the Pearce-Kaye-Hall model (Pearce, Kaye, & Hall, 1982) and confirmed that it would yield these experimental results.…”
Section: Complexitiesmentioning
confidence: 60%
“…We (S. S. Y. Li & McNally, 2015b) conducted a variety of simulations of this action using the Pearce-Kaye-Hall model (Pearce, Kaye, & Hall, 1982) and confirmed that it would yield these experimental results.…”
Section: What Are the Brain Circuits Controlling Variations In Cs Eff...mentioning
confidence: 61%
See 2 more Smart Citations